Propiedades, modificaciones y usos de los almidones, con miras a la obtención de películas biodegradables (2017)
This article analyzes the properties, characteristics and conditions for obtaining polymeric structures; films using starch extracted from various natural sources, such as corn, rice, potatoe, cassava, quinoa, banana. The purpose of this review, on the one hand, is to specify three variables that are closely related to obtaining such structures with biodegradable potential such as: amylose content, particle diameter and gelatinization temperature; and on the other hand, to define the amounts of ingredients for the formulation of starch percentage, plasticizer and drying conditions. The work exposes the effect of each property on the mechanical and optical characteristics of the structure, as well as selecting favorable starches for this application. To achieve these results, the generalities of the starches (of the quinoa starch, in particular), their physicochemical properties and their possible modifications are shown. Finally, the topic is developed based on the information presented.